International Trade, Investment Flows, and Economic Integration between Asia-Pacific and Europe - Andrii Volodymyrovych Shevchenko (Journal of Nusantara Economy, 2025)
This study examines the dynamics of international trade, investment flows, and economic integration between the Asia-Pacific and Europe, with particular emphasis on how institutional arrangements, trade policies, and cross-border investment shape regional economic cooperation in an increasingly fragmented global economy. The research aims to analyze the interactions among trade liberalization, foreign direct investment (FDI), and regional integration, while identifying the principal opportunities and constraints affecting sustainable interregional economic partnerships. Employing a qualitative field research design, the study collected primary data through semi-structured interviews with policymakers, trade officials, business representatives, and investment stakeholders engaged in Asia-Pacific–Europe economic relations. Field observations and an analysis of policy documents, trade agreements, and investment reports complemented these data. The findings reveal that deeper economic integration is driven not only by tariff reductions and investment liberalization but also by regulatory harmonization, digital trade governance, supply chain resilience, and institutional cooperation. Nevertheless, differences in legal frameworks, environmental standards, geopolitical competition, and protectionist policies continue to hinder the optimization of trade and investment flows between the two regions. The study further demonstrates that countries adopting adaptive regulatory reforms, transparent investment policies, and innovation-oriented trade strategies are better positioned to strengthen bilateral and multilateral economic cooperation while improving long-term competitiveness. These findings suggest that sustainable economic integration requires coordinated governance mechanisms extending beyond conventional free trade agreements toward comprehensive frameworks encompassing digital commerce, green investment, and resilient supply chains. This research contributes to the literature on international political economy by offering an empirically grounded field-based perspective on interregional economic integration and by proposing an integrated analytical framework linking trade governance, investment facilitation, and institutional convergence as mutually reinforcing pillars of sustainable economic cooperation between the Asia-Pacific and Europe.